Renal clear cell carcinoma metastasis to salivary glands – a series of 9 cases: clinico-pathological study - Majewska, Hanna; Skálová, Alena; Radecka, Klaudia; Stodulski, Dominik; Hyrcza, Martin; Stankiewicz, Czesław; Biernat, Wojciech (Polish Journal of Pathology, 2016)
Metastatic tumors involving salivary glands arising from the non-head and neck area are very rare. Renal cell carcinoma (RCC) is known for its high propensity for metastasis to unusual localizations. RCC metastasis to the maxillofacial area is an uncommon event (16%), but metastasis to salivary glands is extremely rare. We report a series of 9 such cases retrieved from two institutions. The group included 6 females and 3 males. The age at diagnosis ranged from 60 to 97 years (mean 72.6 years). The tumors involved the parotid gland in 7 cases, and the submandibular and small salivary gland of the oral cavity in 1 case each. The size of tumors ranged from 0.4 to 5 cm. Total parotidectomy with selective neck dissection was performed in 4 cases, while superficial parotidectomy was performed in 1 case and simple resection in 3 cases. Histologically, all the tumors were clear cell renal cell carcinomas, and therefore the differential diagnosis mainly included clear cell variants of salivary gland carcinomas. The parotid gland was the initial manifestation of renal malignancy in 4 of the cases, while in the remaining 5 cases a history of RCC had been known. The salivary gland involvement developed from 11 months to 13 years after the time of diagnosis of the primary tumor. In 2 cases it was the first site of dissemination. Pathologists need to maintain a high index of suspicion for the possibility of metastasis when confronted with oncocytic or clear cell neoplasms developing in salivary glands. RCC, although rare, should be included in this differential diagnosis.